"Horniman Museum and Library Publications" series: zoology and anthropology (1904–1977). Issue 2 (September 2022) - Cain, Joe
Abstract : Horniman Museum and Gardens, London published a group of visitor guides and handbooks from 1904 to 1977 under the series title "Horniman Museum and Library Publications" to accompany the permanent galleries. This paper presents a bibliography for the series, which covered subjects in zoology and anthropology. The series included 16 publications. Many had multiple editions. Authors were not always identified explicitly, and attribution was assigned to the institution. This paper identifies authors and other notable contributors for each volume. The Horniman stopped assigning new publications to the series at the end of the 1930s; however, new guides and handbooks continued to be published in similar fashion. Some of those later publications asserted continuity, claiming to be new editions. Others did not. Both continuities and breaks reveal aspects of work within the museum environment as well as trends in British museum engagement with its audiences. For instance, simplification is a profound trend over successive editions.